The Vertical Profile of Phosphate on the Baru Lake in Buluh Cina Village Siak Hulu Subdistrict Kampar District - Amat M. Siregar; Asmika H. Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done on the Baru Lake Buluh Cina Village Siak Hulu SubdistrictDistrict Kampar from March - April 2013. This research aims to understand the vertical profile ofphosphate in this lake. The researh used survey method. Sample were taken horizontally in threestation and vertically in three sampling point. The water quality parameters measured were pH,dissolved oxygen (DO), based on transparancy, temperature and depth.The concentration of phosphate was 0,016 - 0,113 mg/l. The value of pH was 6. Theconcentration of dissolved oxygen (DO) was 2,6 – 5,47 mg/l. Based on transparancy was 47,0 -55,8 cm. Temperature was 29 – 30,3ºC. Depth was 346 – 409 cm. Phosphate consentration insurface was 0,016 – 0,037 mg/l, while in bottom was 0,063 – 0,113 mg/l. The vertical profile ofphosphate in bottom was higher than in the surface. The parameters of water quality were observedstill sustain the aquatic organism life.Keywords: phosphate, vertical profile, Baru Lake